Examining the Impact of Smartphone Dependency on Anxiety and Depression Symptoms Among Individuals Aged 25-35 Years Old: A Quantitative Study - Seifert, Rachel Anne; Avena, Nicole; Rabas, Audrey; Domingo, Aldwin (Advances in Social Sciences Research Journal, 2024)
Nomophobia is characterized by a pervasive anxiety experienced when an individual is separated from their smartphones. Prior research has documented the prevalence of nomophobia along with the impact of nomophobia in both anxiety and depression for samples of college or university aged individuals. In contrast, there is only scarce or emerging research on the prevalence and mental health impact (anxiety and depression) of smartphone dependency among adults aged between 25 and 35 years old in the year 2020. The target age of participants for this quantitative study was chosen because they would have been the early adopters of smartphones when smartphones were initially available for the general population use starting in 2007. This research study showed that 64% of the sample of 25 and 35 years old participants had a diagnosable level of Nomophobia. Moreover, this research study showed that corresponding increases in self-reported Nomophobia scores among 24-35 year old participants had a corresponding increase in both their self-reported anxiety and depression scores. The research study concludes by proposing further longitudinal research on the effects of Nomophobia, further examination of the causal relation between the variables examined in this study, and recommending educational policies that encourage digital balance for using smartphone use among 24-35 year olds.